2024
DOI: 10.3389/fnagi.2024.1378576
|View full text |Cite
|
Sign up to set email alerts
|

Clathrin mediated endocytosis in Alzheimer’s disease: cell type specific involvement in amyloid beta pathology

Sierra Jaye,
Ursula S. Sandau,
Julie A. Saugstad

Abstract: This review provides a comprehensive examination of the role of clathrin-mediated endocytosis (CME) in Alzheimer’s disease (AD) pathogenesis, emphasizing its impact across various cellular contexts beyond neuronal dysfunction. In neurons, dysregulated CME contributes to synaptic dysfunction, amyloid beta (Aβ) processing, and Tau pathology, highlighting its involvement in early AD pathogenesis. Furthermore, CME alterations extend to non-neuronal cell types, including astrocytes and microglia, which play crucial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 177 publications
(202 reference statements)
0
1
0
Order By: Relevance
“…As such, disruption of CME function is associated with many diseases ( McMahon and Boucrot, 2011 ; Schreij et al, 2016 ). In humans with AD, genetic links have been made to Adaptor Related Protein Complex 2 ( AP2 ) and Phosphatidylinositol Binding Clathrin Assembly Protein ( PICALM ) ( Raj et al, 2018 ; Azarnia et al, 2019 ) and many proteins involved in CME have reported changes at the RNA and protein level over a wide variety of brain regions ( Yao et al, 1999 , 2000 , 2003 ; Cao et al, 2010 ; Jaye et al, 2024 ). There are many cellular functions disrupted in AD that are downstream of CME or use CME machinery.…”
Section: Introductionmentioning
confidence: 99%
“…As such, disruption of CME function is associated with many diseases ( McMahon and Boucrot, 2011 ; Schreij et al, 2016 ). In humans with AD, genetic links have been made to Adaptor Related Protein Complex 2 ( AP2 ) and Phosphatidylinositol Binding Clathrin Assembly Protein ( PICALM ) ( Raj et al, 2018 ; Azarnia et al, 2019 ) and many proteins involved in CME have reported changes at the RNA and protein level over a wide variety of brain regions ( Yao et al, 1999 , 2000 , 2003 ; Cao et al, 2010 ; Jaye et al, 2024 ). There are many cellular functions disrupted in AD that are downstream of CME or use CME machinery.…”
Section: Introductionmentioning
confidence: 99%